FRI0048 Interleukin-6 increases the number of osteoclast precursors in femur bone marrow via up-regulation of sphingosine-1-phosphate receptor 2 in inflammatory arthritic mice. (23rd January 2014) - Hashizume, M.; Tanaka, K.; Yoshida, H.; Suzuki, M.; Shiina, M.; Mori, K.; Mihara, M.
Abstract : Background: Rheumatoid arthritis (RA) is associated with an increased risk of osteoporosis and fractures. A number of factors such as menopause, glucocorticoid use, and high RA disease activity are associated with an increased risk of osteoporosis. Several studies have demonstrated a link between osteoporosis and pro-inflammatory cytokines such as interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α). Recent studies have shown that sphingosine-1-phosphate (S1P) controls the dynamic intermigration of osteoclast precursors (OCPs) between the blood and bones, in part via the S1P receptor 2 (S1PR2) expressed on the surface of OCPs. Inhibition of S1PR2 function changed the dynamics of OCP migration and relieved osteoporosis in a mouse model of bone loss. However, it is not yet understood whether pro-inflammatory cytokines affect the expression and function of S1PR2 in the course of bone loss. Objectives: The purpose of this study was to investigate whether IL-6 and TNF-α regulate the expression and function of S1PR2, and whether they have any influence on the localization of OCPs in the course of bone loss. Methods: OCPs (CD11b + Gr-1 low+med ) were isolated from DBA/1J mice bone marrow by using a cell sorter, and were stimulated with IL-6 or TNF-α. S1PR2 mRNA expression in OCPs was measured by real-time PCR. To examine the function of S1PR2, S1P-directed chemotactic activity was evaluated by using a Transwell plate. DBA/1J mice were immunized intradermally with bovine type II collagen (Day 0), and anti-mouse IL-6 receptor antibody and control IgG were administered intraperitoneally on the same day. On Days 8 and 15, femurs were excised and the trabecular bone volume (bone volume/tissue volume) of the distal femur was analyzed using microfocus computed tomography. The number of OCPs in the femur bone marrow was counted by flow cytometry. S1PR2 expression in OCPs from immunized mice was measured by real-time PCR. Results: IL-6 induced S1PR2 in OCPs in a dose-dependent manner, but TNF-α did not induce S1PR2. Because S1PR2 negatively regulates chemotaxis in the direction of S1P, which is rich in blood, we examined the migratory response of OCPs stimulated by IL-6 in the direction of S1P. In the presence of IL-6, S1P-directed chemotaxis of OCPs in the direction of S1P was decreased by 64% compared with medium control. Trabecular bone volume in immunized mice was decreased by more than 9% on Day 8 and was significantly decreased by 33% on Day 15 compared with normal mice. The number of OCPs in femur bone marrow significantly increased in immunized mice at Day 8 and Day 15; moreover, the expression of S1PR2 in immunized mice was significantly increased compared with normal mice. Treatment of immunized mice with anti-IL-6 receptor antibody decreased the number of OCPs in femur bone marrow by 25% and the expression of S1PR2 by 27%; however no changes were seen following treatment with control IgG. Conclusions: The results demonstrated that IL-6 increases the number of OCPs in femur bone marrow via up-regulating S1PR2, and plays a crucial role in bone loss induced by inflammation. Disclosure of Interest: None Declared